ANALISIS PUBLIC RELATION, ADVERTISING, DAN DIRECT MARKETING TERHADAP LOYALITAS PELANGGAN ES.TEH INDONESIA - Wiyarno; Erna Apriani; Indra Permana; Fachrial Banyu Asmoro (POLITEKNIK LP3I JAKARTA, 2025)
Es.teh Indonesia is a franchise engaged in the beverage sector, where Es. Indonesia has a reasonably large name in the beverage sector; the development of Es.teh Indonesia is relatively fast and has been around for a long time, so an evaluation is needed regarding marketing strategies, promotions, and those that cause significant customer loyalty. From these problems, the purpose of this study was to examine the effect of Public Relations, Advertising, and Direct Marketing on Customer Loyalty of Es.teh Indonesia. The method of analyzing this research uses a quantitative descriptive approach to look for influential relationships between research variables; the sample taken is Indonesian Es.teh customers with a purposive sampling method of 100 respondents, and the research data analysis technique uses SEM (Stuctural Equation Modelling). The results showed that public relations significantly affected customer loyalty, then advertising and direct marketing variables had no effect on customer loyalty in Indonesia.